Penerapan Reinforcement Learning dan Deep Learning: Studi Kasus pada Mahasiswa D4 Politeknik Prasetiya Mandiri - Ilsa Palingga Ninditama; Netti Herwati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The development of artificial intelligence (AI) technology in education is increasingly rapid, especially in the application of Reinforcement Learning (RL) and Deep Learning (DL) in the learning process. However, the application of this technology still faces various challenges, such as limited student understanding of basic algorithms and the effectiveness of AI-based systems in improving programming skills. This study aims to analyze the implementation of RL and DL in the learning of D4 Multimedia Engineering Technology students at Prasetiya Mandiri Polytechnic and identify the challenges and benefits. This study uses a qualitative approach with a case study method, involving 20 students as research subjects. Data were collected through observations, in-depth interviews, and documentation studies. The results of the study show that RL and DL can improve students’ understanding of programming, although there are still obstacles such as difficulties in adapting to AI-based systems. In conclusion, AI technology has the potential to increase the effectiveness of learning, but it needs the right strategy in its application.